2000
DOI: 10.5380/avs.v5i1.3879
|View full text |Cite
|
Sign up to set email alerts
|

AVALIAÇÃO DAS TAXAS DE CRESCIMENTO DE Farfantepenaeus paulensis Pérez-Farfante, 1967 EM VIVEIROS DE CULTIVO

Abstract: RESUMO -O presente estudo surgiu a partir da necessidade de se avaliar as taxas de crescimento do camarão-rosa Farfantepenaeus paulensis ao longo do ano, em cultivos realizados em uma fazenda localizada no Estado do Paraná, Brasil. Para isso, foi desenvolvido um índice de crescimento (ICr), que quantifica as taxas de crescimento dos camarões em relação ao ganho de peso por semana (GPS), medido em g/semana, e o ganho percentual de peso por semana (GPPS), medido em %/semana. O índice proposto pode ser descrito p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…From the second biometry until the end of the experiment, daily growth rates were similar between treatments. Normally, the absolute growth rates and the weight percentage are inversely proportional (Ostrensky & Pestana, 2000). This was evident in the present study, especially in the first biometry, when the compensatory growth was observed in shrimps of the LTN treatment.…”
Section: Grow Out Periodsupporting
confidence: 78%
See 1 more Smart Citation
“…From the second biometry until the end of the experiment, daily growth rates were similar between treatments. Normally, the absolute growth rates and the weight percentage are inversely proportional (Ostrensky & Pestana, 2000). This was evident in the present study, especially in the first biometry, when the compensatory growth was observed in shrimps of the LTN treatment.…”
Section: Grow Out Periodsupporting
confidence: 78%
“…The specific growth rate (SGR) is a parameter typically used to identify compensatory growth. For example, Wu et al (2001) used SGR in an experiment on food restriction and refeeding and also in an experiment on protein restriction of Fenneropenaeus chinensis; Ostrensky & Pestana (2000) used SGR to evaluate growth rates of F. paulensis in grow out ponds; Kumlu & Kir (2005) used SGR to evaluate growth and survival of Penaeus semisulcatus in temperate climates.…”
Section: Grow Out Periodmentioning
confidence: 99%
“…Este aumento da produção e produtividade da carcinicultura no Brasil tem sido atribuído à própria capacidade da espécie cultivada de se adaptar às condições edafoclimáticas (ABCC, 2013), à expansão da área cultivada (RODRIGUES e BORBA, 2013), ao uso de produtos biotecnológicos (JONES e DOURADO, 2003), à alta densidade de estocagem dos viveiros (FONSECA, 2005) e à melhoria da gestão da propriedade (SANTOS et al, 2015). Porém, a qualidade inferior dos insumos pode ser um fator limitante para o crescimento da produtividade do cultivo de camarão (OSTRENSKY e PESTANA, 2000).…”
Section: Introductionunclassified